Empowering Smallholder Dairy Farmers through Product Diversification: A Sustainable Value-Addition Strategy in Pasuruan - Sholihah, Dewi Deniaty; Ramadhani, Mirza; Yuniati, Yuyun; Adelia, Kezia; Perwirani, Nindya Ayu Leonita (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This condition impacts the low added value received and consequently affects the farmers’ welfare. This community service activity aims to empower farmers by diversifying fresh milk products into mozzarella cheese and yoghurt, thereby increasing added value. The method used is Participatory Rural Appraisal (PRA), which emphasizes active participation of partners in the process of problem identification, needs analysis, and solution formulation. The stages of activities include the socialization of business feasibility and marketing of processed milk products, technical training in mozzarella cheese and yogurt production, mentoring, and production monitoring. The results show that farmers are able to produce both products with good quality standards and improve their skills in processing and packaging. In addition, there is an increased awareness among farmers of the importance of product innovation in maintaining business sustainability. This activity also opens new marketing opportunities through local and digital networks, thereby contributing to the increase of farmers’ income. Contribution to Sustainable Development Goals (SDGs):SDG 1: No PovertySDG 8: Decent Work and Economic GrowthSDG 12: Responsible consumption and production